Achromobacter xylosoxidans bacteremia and cellulitis: a report of a case - Dai, Julia (Pediatr Dermatol, 2015)
Achromobacter xylosoxidans is a rare, opportunistic infection most commonly encountered among immunocompromised patients during hospitalization. Primary uncomplicated bacteremia, catheter-associated infections, and pneumonia have been reported as the most common clinical presentations, but skin and soft tissue infections from A. xylosoxidans are rare. We describe a case of A. xylosoxidans presenting as cellulitis and bacteremia in an immunocompromised patient.